CSF-1/CSF-1R targeting agents in clinical development for cancer therapy. (August 2015) - Ries, Carola H; Hoves, Sabine; Cannarile, Michael A; Rüttinger, Dominik
Highlights: TAM promote tumor growth and efficiently suppress immune effector cells. Targeting TAM via the CSF-1/CSF-1R pathway is an attractive therapy for cancer. Can in vitro differentiated macrophages reflect patient-derived TAM? TAM depletion combined with standard- or immuno-therapies will be the way forward. Abstract : Macrophage infiltration has been identified as an independent poor prognostic factor for several cancer entities. In mouse tumor models macrophages orchestrate various tumor-promoting processes. This observation sparked an interest to therapeutically target these plastic innate immune cells. To date, blockade of colony stimulating factor-1 or its receptor represents the only truly selective approach to manipulate macrophages in cancer patients. Here, we discuss the currently available information on efficacy and safety of various CSF-1/CSF-1R inhibitors in cancer patients and highlight potential combination partners emerging from preclinical studies while considering the differences between mouse and human macrophage biology.